Bioactive glasses for bone tissue engineering: a bibliometric study of the top 100-most cited papers - dos Reis-Prado, Alexandre Henrique; de Souza, Joyce Rodrigues [UNESP]; de Sousa Trichês, Eliandra; de Abreu Furquim, Elisa Mara [UNESP]; Dal-Fabbro, Renan; Benetti, Francine; Bottino, Marco C. (Springer Nature, 2024)
Using bioactive glasses (BGs) for bone reconstruction is a promising and expanding field of investigation in regenerative medicine. Therefore, the aim of this study was to assess the key features of the 100 most cited papers on BG in bone tissue engineering through bibliometric measures. A search was conducted in the Web of Science citation indexing database until October 2023. Three researchers performed study selection and data extraction. Data extraction included publication title and year, authors, number of citations and mean number of citations, institution, country and continent, study design, journal, keywords, and bioactive glasses. Citation counts were also collected in Google Scholar and Scopus databases. Graphical bibliometric networks were created using VOSviewer software. The number of citations of the 100 most cited articles ranged from 118 to 1836, with ten papers cited more than 400 times. Articles were mostly published between 2011 and 2012. Most papers, comprising 72 in vitro studies, originated from the United States (n = 22) and were published in Biomaterials (27%). Aldo Boccaccini was the most cited author (n = 17; 6332 citations). The most prolific institution was Imperial College London (n = 19; 7073 citations), followed by Missouri University (USA; n = 7; 2494 citations). Bioactive glass was the most frequent keyword, with 46 occurrences. Laboratory-based studies, primarily conducted in the United States, evaluating the physicochemical, osteogenic properties, and antibacterial activity of silica-based bioactive glasses such as 45S5 have been the most cited thus far.
Keywords: Bibliometrics; Biocompatible materials; Bioglass; Databases; Tissue engineering